EVOLUTION OF SPEED IN SECONDARY SCHOOL STUDENTS - Gheorghe LUCACIU; Sergiu HADADE; Luminița Anca DEAC (Editura Universităţii din Oradea, 2019)
Given the multilateral development of the human personality, physical education is an integral part of the training and education of the youth, contributing to the successful fulfillment of the general tasks in the direction of human formation in society. The objective and natural connection with the other components of multilateral education is determined by the social needs, by the context in which people must develop from all points of view, both physically and mentally, in order to be able to work efficiently, creatively. Among the motor qualities/capacities, the forms of manifestation of speed extend their manifestation area either on the development of coordination, force and not least on the capacity of the body to sustain an intense physical effort in order to achieve an objective in the shortest time with a relatively constant efficiency, which justifies the interest of those who approach the subject. Given the biological and physiological conditionality regarding the forms in which the speed is manifested, the moment when the pedagogical intervention on their evolution occurs is one of great importance. The present paper aims to highlight how speed evolves as a result of the effects of practicing physical education.